2009
DOI: 10.1101/lm.1289809
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the BK channel impedes acquisition of trace eyeblink conditioning

Abstract: Big-K+ conductance (BK)-channel mediated fast afterhyperpolarizations (AHPs) following action potentials are reduced after eyeblink conditioning. Blocking BK channels with paxilline increases evoked firing frequency in vitro and spontaneous pyramidal activity in vivo. To examine how increased excitability after BK-channel blockade affects learning, rats received bilateral infusions of paxilline, saline, or nothing into hippocampal CA1 prior to trace eyeblink conditioning. The drug group was slower to acquire t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…to the dorsal hippocampus (Matthews and Disterhoft 2009). If a spherical volume of diffusion is assumed, then a compound will diffuse and occupy about 0.015 cm 3 (or ϳ15 L) of space.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…to the dorsal hippocampus (Matthews and Disterhoft 2009). If a spherical volume of diffusion is assumed, then a compound will diffuse and occupy about 0.015 cm 3 (or ϳ15 L) of space.…”
Section: Resultsmentioning
confidence: 98%
“…Guide cannulae, made of 26-gauge stainless steel tubing, were bilaterally implanted in the dorsal hippocampus (3.6 mm posterior and 2.0 mm lateral from bregma, 1.9 mm below the dura) and cemented in place with dental acrylic. A previous report using the same stereotaxic coordinates demonstrated that the diffusion of 1 L of ibotenic acid injected into the dorsal CA1 region via guide cannulae was limited to the dorsal hippocampus (Matthews and Disterhoft 2009). Although not identical in structure, the spread of NS309 should be similar to that observed with ibotenic acid and be limited to the dorsal hippocampus.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown recently that pharmacological inactivation of K Ca channels leads to learning impairment (143), and deficits in learned behavior have also been described in rodents after 14 days of IH (243). It is perhaps not surprising then, that exposure of adult rat hippocampal neurons to IH for several days decreased the activity of K Ca channels (219,220).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…They are involved in motor coordination [59], learning and memory [28,[60][61][62], circadian rhythm [63][64][65][66], regulation of respiration [67][68][69], hearing [70], and pain [71][72][73][74]. BK channels confer neuroprotection [75][76][77][78].…”
Section: Introductionmentioning
confidence: 99%